2010
DOI: 10.1038/ismej.2010.131
|View full text |Cite
|
Sign up to set email alerts
|

In situ dynamics of O2, pH and cyanobacterial transcripts associated with CCM, photosynthesis and detoxification of ROS

Abstract: The relative abundance of transcripts encoding proteins involved in inorganic carbon concentrating mechanisms (CCM), detoxification of reactive oxygen species (ROS) and photosynthesis in the thermophilic cyanobacterium Synechococcus OS-B 0 was measured in hot spring microbial mats over two diel cycles, and was coupled with in situ determinations of incoming irradiance and microenvironmental dynamics of O 2 and pH. Fluctuations in pH and O 2 in the mats were largely driven by the diel cycle of solar irradiance,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
55
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 68 publications
5
55
0
Order By: Relevance
“…JA-3-3Ab, an enzyme involved in neutralization of reactive oxygen species (ROS), was observed. Its presence in this high-light sample supports previous OS studies on the diel expression of enzymes involved in cyanobacterial ROS defense (9). These studies determined that mRNA transcripts for SOD increased in high light, presumably to counteract the increase in ROS from high irradiance and increased oxygen levels.…”
supporting
confidence: 72%
“…JA-3-3Ab, an enzyme involved in neutralization of reactive oxygen species (ROS), was observed. Its presence in this high-light sample supports previous OS studies on the diel expression of enzymes involved in cyanobacterial ROS defense (9). These studies determined that mRNA transcripts for SOD increased in high light, presumably to counteract the increase in ROS from high irradiance and increased oxygen levels.…”
supporting
confidence: 72%
“…A change in the reference potential might cause such effects, while it is not possible to obtain an increase in pH microsensor sensitivity significantly above the 58 mV per pH unit determined in the calibration. The measured pH at 2-to 3-mm depth was 1.4 pH unit below the water reading at 4:00 and as other investigations (48)(49)(50) found early morning pH values in the overlying water from 7.7 to 7.9 in similar settings, it can be concluded that the pH in the mat must have been below 6.5. Our site was far outside the main flow channel, and the overlying water pH might have been further lowered as seen in our data (pH 7.1 at 4:00) by a long contact time with the mat, resulting in a pH minimum in the mat considerably below 6.5.…”
Section: Discussionmentioning
confidence: 75%
“…This combined approach enabled us to (i) discover new major populations of uncultivated community members; (ii) explore differences in the functional potential of native populations as compared with closely related isolates and (iii) observe differences in genomic content and synteny among closely related populations. This study also created a foundation for a companion study using metatranscriptomics to describe in situ gene expression in the chlorophototrophic taxa , the results of which strongly support our functional inferences and expand upon in situ gene expression studies of these mats (Steunou et al, 2006(Steunou et al, , 2008Jensen et al, 2011).…”
Section: Introductionmentioning
confidence: 76%